Structural, Mossbauer spectra and magnetic properties of Ni(1-x) Cdx Fe2O4 by solid state Reaction method - Abdulsamee Fawzi Abdul Aziz Al-Bayati (Tikrit Journal of Pure Science)
The preparation of Ni-Cd ferrite having the chemical formula Ni(1-x)CdxFe2O4 where x varies from 0, 0.1, 0.2, 0.3, 0.4, and 0.5 were synthesized by solid state reaction method. The X-ray analysis shows the existence of single phase spinel structure with increase of lattice parameter and density with increasing Cd contents were as the porosity decreases. The particle size was calculated by X-ray broadening studies. The Vickers hardness of Ni-Cd ferrite system variation between 532 to 568.6. The increase in hardness of composites results from increased Cd-content. The Atomic Force Microscopy (AFM) showed that the average grain size was increases with the increase in Cd content. The variation of dielectric constant, loss tangent and AC conductivity as a function of frequency in frequency range 100Hz-5MHz was studied. The dielectric constants decreases with increasing frequency for all the samples and follow the Maxwell-Wagner's interfacial polarization. The Hall coefficient was found to be positive. It demonstrates that the majority of charge carriers of p-type. The magnetic properties of Ni(1-x)CdxFe2O4 ferrites were strongly affected by the Cd content. The Mossbaure spectra show canted spin structure for all the samples.